Intracerebral recording of cortical activity related to self-paced voluntary movements: a Bereitschaftspotential and event-related desynchronization/synchronization. SEEG study - Sochůrková, Daniela; Rektor, Ivan; Jurák, Pavel; Stancák, Andrej (Experimental brain research, 2006)
To analyze the distribution of the cortical electrical activity related to self-paced voluntary movements, i.e. the movement-related readiness potentials (Bereitschaftspotential, BP) and the event-related desynchronization (ERD) and synchronization (ERS) of cortical rhythms using intracerebral recordings. EEG was recorded in 14 epilepsy surgery candidates during preoperative video-stereo-EEG monitoring. Subjects performed self-paced hand movements, with their right and left fingers in succession. EEG signals were obtained from a total of 501 contacts using depth electrodes located in primary and nonprimary cortical regions. In accordance with previous studies, BP was found consistently in the primary motor (M1) and somatosensory (S1) cortex, the supplementary motor area (SMA), and in a few recordings also in the cingulate cortex and in the dorsolateral prefrontal and premotor cortex. ERD and ERS of alpha and beta rhythms were also observed in these cortical regions. The distribution of contacts showing ERD or ERS was larger than the distribution of those showing BP. In contrast to BP, ERD and ERS frequently occurred in the lateral and mesial temporal cortex and the inferior parietal lobule. The number of contacts and cortical regions showing ERD and ERS and not BP suggests that the two electrophysiological phenomena are differently involved in the preparation and execution of simple voluntary movements. Substantial differences between BP and ERD in spatial distribution and the widespread topography of ERD/ERS in temporal and higher-order motor regions suggest that oscillatory cortical changes are coupled with cognitive processes supporting movement tasks, such as memory, time interval estimation, and attention.
Keywords: dospělí; mozek; Humans; Brain; Supine Position; Functional Laterality; elektroencefalografie; Motor Activity; pohybová aktivita; mužské pohlaví; mapování mozku; Evoked Potentials; evokované potenciály; funkční lateralita; Adult; Adolescent; supinační poloha; záchvaty; Epilepsy; Electroencephalography; Seizures; ženské pohlaví; epilepsie; Brain Mapping; lidé; mladiství; Male; Female